Keratinolytic Protease Production by Bacillus Cereus Strain Ps03 under Submerged Fermentation: Optimization and Characterization - BalaKumaran, M.D.; Santhi, R. (International Journal of Applied Sciences and Biotechnology, 2016)
In the present study, chicken feather powder was screened for its application as the substrate for the production of keratinolytic protease by Bacillus subtilis strain PS03. Bacillus subtilis produced a high level of keratinolytic protease using chicken feather powder as substrate. With feather powder as substrate, physical factors such as incubation time, pH and temperature were optimized for increased keratinolytic protease production by Bacillus subtilis. The enzyme production was enhanced when using maltose as carbon source and yeast extract as nitrogen sources. SDS-PAGE analysis indicated the molecular weight of 46 kDa of the partially purified keratinolytic protease. The keratinolytic protease enzyme was stable over a pH range of 6 – 9 and temperature range of 35 - 50°C with maximum activity at pH 9 and 40°C. Based on the results, the use of feather powder as substrate for keratinolytic protease production is cost effective and is easy to scale up. Considering the availability and cost, chicken feather powder is considered as an ideal substrate for keratinolytic protease production in an industrial point of view. Int J Appl Sci Biotechnol, Vol 4(3): 397-401